2019
DOI: 10.1097/cnj.0000000000000496
|View full text |Cite
|
Sign up to set email alerts
|

Tattoos in Nursing

Abstract: Tattoos have become increasingly popular in the U.S. among the general population. Furthermore, the popularity of body art, primarily tattoos, among nursing students generates issues about professionalism in academics and in clinical settings. Nursing faculty are faced with conflicting views on cultural awareness, professionalism, and self-expression. With nursing viewed as one of the most trusted professions, the policy of covering tattoos should be discussed, and more research is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 6 publications
0
13
0
1
Order By: Relevance
“…Empirical studies included 7 US survey studies,22–28 an online observational study from Sweden,19 and a bacteriological study from Japan 29. Nonresearch articles consisted of 4 letters to the editor9,12,20,30 and 6 commentary and opinion pieces 11,18,31–33. Other nonresearch articles included 2 case studies,8,16 a legal commentary,34 2 specific to nursing issues,10,17 and an editorial 35.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Empirical studies included 7 US survey studies,22–28 an online observational study from Sweden,19 and a bacteriological study from Japan 29. Nonresearch articles consisted of 4 letters to the editor9,12,20,30 and 6 commentary and opinion pieces 11,18,31–33. Other nonresearch articles included 2 case studies,8,16 a legal commentary,34 2 specific to nursing issues,10,17 and an editorial 35.…”
Section: Resultsmentioning
confidence: 99%
“…Eriksson et al19 identified personal meaning as an important concept, as well as a need to develop an understanding of body art in nursing research and practice. The consideration of personal meaning behind body art was a predominant subtheme in nonresearch literature tied to level of acceptability 8,16–18,20,30,33,37. EBP considerations discussed the need for unbiased nursing for those with body art and reciprocation for nurses who have tattoos and piercings 37.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…provedenom na studentima sestrinstva posjedovanje tetovaže predstavlja probleme u akademskim ustanovama, ali i u klinikama. Zaključci istraživanja isto tako navode preporuke studentima sestrinstva za prekrivanje vidljivih tetovaža [13].…”
Section: Raspravaunclassified
“…A 2018 study found that both medical students and doctors sometimes perceive visible tattoos as deterring from a doctor’s professionalism 1. Numerous respondents in a 2019 survey of nurses reported that despite the positive patient-professional connections they forged with the help of their tattoos, their workplace had a “no visible body art” policy because of concerns about professionalism 2. One nurse specifically highlighted the need for healthcare professionals to support each other more and introduce policy changes to protect professionals’ right to self-expression.…”
mentioning
confidence: 99%